Analisis Distribusi Zakat di Indonesia: Porsi Penyaluran Zakat Kepada Asnaf Pada Tahun 2023 - Sandie, Sandie; Abdillah, Abdillah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to analyze the distribution of zakat in Indonesia, focusing on the portion of zakat distribution to each asnaf in 2023. Zakat, as one of the pillars of Islamic economics, has an important role in reducing social inequality and improving people's welfare. The distribution of zakat in Indonesia is managed by various zakat institutions, one of which is Baitulmaal Munzalan Indonesia. This study uses a descriptive qualitative approach with content analysis to describe the distribution of zakat to five asnaf, namely fakir, poor, fi sabilillah, muallaf, and ibn sabil. The data used was obtained from 35 branches of Baitulmaal Munzalan throughout Indonesia in 2023. Data analysis was carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the allocation of zakat is more given to the poor and Fi Sabilillah, while the Fakir, Muallaf, and Ibn Sabil get a lower allocation. This study also identifies various factors that affect the imbalance in zakat distribution, such as limited data collection, priority of zakat institutions, and socio-economic factors. Recommendations are given to increase the equitable distribution of zakat in the future